Giant Seafloor Depressions Caused by Slope Failures and Bottom Currents on the Namibia Continental Margin. (29th June 2021) - Wenau, S.; Spiess, V.; Zabel, M.
Abstract: More than 100 circular, elongate or crescent‐shaped very large seafloor depressions were found on the southern Namibian continental margin in water depths between 900 and 1700 m. These depressions show extraordinary sizes of up to 3 km diameter and 180 m depth. Multichannel seismic and bathymetric data show the influence of bottom currents on their morphology through prograding infills on the upcurrent and erosion on the downcurrent flanks, thus creating a crescent morphology in the largest depressions. Although their seafloor morphology resembles pockmarks related to seafloor fluid seepage, no indications for an active fluid flow system were observed in the area. Some depressions show extensive underlying cut‐and‐fill sequences that could be traced down to slope failure structures and deposits at depth. A correlation to ODP drill site 1085 indicates a continuous development of seafloor depressions for ∼10 Ma, documented by successive stages of infilling, erosion and size variations. Analysis of the seismic reflection data suggests that these depressions formed through the interaction of bottom currents with existing seafloor morphology. The equilibrium seafloor of the continental margin was initially disturbed by mass‐wasting events, common occurrences in the region. Subsequently, ongoing sedimentation in their vicinity was affected by ocean bottom currents, leading to the preservation and constant re‐shaping of seafloor depressions until recent times. This study thus highlights the ability of continental slope sedimentation under bottom‐current influence to produce unique seafloor features over long geological time scales. Key Points: Giant seafloor depressions are formed by an interaction of bottom currents and pre‐existing seafloor topograph Initial seafloor depressions are initiated by slope failure processes